PENGARUH DISIPLIN KERJA, MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA PADA PT TIRTA PUTRA MALINDO SEJATI DI KOTA BATAM - Alice; Nainggolan, Nora Pitri (LPPM Universitas Putera Batam, 2022)
In this recent day when the intensity is keep growing, there are many threats that must be faced. Companies must be able to compete by adapting to internal and external changes so that the company is more advanced. With this, the company seeks different ways in order to improve the company itself and increase job satisfaction. This study aims to knowing the effect of work discipline, work motivation and work environment together on job satisfaction at PT Tirta Putra Malindo Sejati. This study is using a saturated sampling technique with a population and the samples taken both are 130 employees. Data for this study was obtained through distributing questionnaires. Data analysis in this study used the multiple linear regression analysis, the data quality test used the validity test and reliability test, the classical assumption test used the normality test, multicollinearity test and heteroscedasticity test and the influence test used the multiple linear regression analysis and coefficient of determination analysis, while the hypothesis test used the t test and F test by utilizing the SPSS program version 25. The results showed that work discipline, work motivation and work environment together affect job satisfaction at PT Tirta Putra Malindo Sejati.